A study on color conspicuity and color harmony of wayfinding signs according to outdoor environment types. Issue 6 (30th June 2022) - Yi, Ji Hyun; Jeon, Junryeol
Abstract: Wayfinding signs must have prominent visibility in the environment to provide people with the information they need to navigate to an intended destination. Therefore, designers seek to design signs that are clearly visible while esthetically harmonious with the ambient environment. To find highly conspicuous colors, 1632 images showing combinations of various colors and environments were created. And then evaluation factors such as sign conspicuity, color contrast, color harmony, sign color preference, and expected sign usability were tested with 33 designers. Through statistical analysis of experimental results, the colors with high conspicuity and harmony were organized in different types of environments, and all correlations between the evaluation factors were analyzed. The results showed that all evaluation factors had a significantly high correlation except color harmony. Based on these results, we conclude that when designing a sign, it should focus on increasing the sign conspicuity by using color difference rather than color harmony between the sign and the ambient environment. Abstract :